2022
DOI: 10.1136/fmch-2021-001481
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in health service use among women with poor mental health: a 7-year follow-up

Abstract: ObjectiveWomen suffering from mental health problems require varied needs of mental health service utilisation. Transition between general practitioner and mental health services use are available through the Better Access Scheme initiative, for those in need of treatment. The study’s aim was to identify trajectories of mental health service utilisation by Australian women.DesignThe Australian Longitudinal Study on Women’s Health data linked to the administrative medical claims dataset were used to identify su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Additionally, mental health inequalities also exist by gender and economic level 39 which might be reflected by service use and differences in OOP costs for services. Further, understanding the barriers and facilitators may help in improving referral pathways and in coordinating models of care suitable for each individual's mental health needs and financial standing 40–43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, mental health inequalities also exist by gender and economic level 39 which might be reflected by service use and differences in OOP costs for services. Further, understanding the barriers and facilitators may help in improving referral pathways and in coordinating models of care suitable for each individual's mental health needs and financial standing 40–43 …”
Section: Discussionmentioning
confidence: 99%
“…Further, understanding the barriers and facilitators may help in improving referral pathways and in coordinating models of care suitable for each individual's mental health needs and financial standing. [40][41][42][43] Treatment dependent recovery is most effective where existing services provide personalised measured care via the use of technology and coordinated care to reduce mental health progression. 44 Skinner et al identified the need for modifying service availability and accessibility of mental health care systems to increase early recovery rates and reduce the proportion of people whose condition declines.…”
Section: Discussionmentioning
confidence: 99%